Awareness About Dental Amalgam Among Turkish Dentists and Patients: A Questionnaire and Search Engine Based Cross-Sectional Study - Özlem Erçin; Begüm Berkmen; Elif Durukan; Neslihan Arhun (Elsevier, 2021)
Objectives: There has been considerable controversy concerning the health risks and benefits of using mercury-containing amalgam. This study aimed to evaluate the Turkish dentists' and patients' preference and opinion about amalgam and to assess Internet search trends about amalgam. Methods: The study consists of three stages. The first two stages of the study are cross-sectional studies to verify both the patients' perception with amalgam restorations and dentists' attitudes regarding the use of dental amalgam. The third stage of the study evaluated the Internet search trends of Turkish people about mercury and amalgam related concerns between 2004 and 2018. Results: A total of 320 patients (180 female, 140 male) and 1,211 dentists (533 female, 678 male) participated in this study. Majority of the patients have no idea about the type of dental restorations and effect of dental materials on their health. 188 (58.8%) participants stated that they would not prefer amalgam restoration in their teeth as amalgam is unaesthetic. A total of 24% (291) of the dentists used amalgam routinely; 9.5% (156) of them used amalgam rarely, and 63.1% (764) did not use amalgam at all. The reason for not using amalgam included the patients' desire and unaesthetic properties. According to the Internet search trends, Turkish people do not know as much about amalgam as people in the rest of the world. Conclusion: Awareness about dental amalgam is low among patients studied. Although dentists do not use dental amalgam frequently, they disagree on banning dental amalgam.